KINERJA KONSTRUKSI KISI BETON PADA LERENG BATU LUNAK - Rudy Febrijanto; Riyadi Salim (Direktorat Bina Teknik Jalan dan Jembatan, 2019)
ABSTRACT Infrastructure development especially roads in mountainous and hilly areas is inseparable from cut and fill. The common slope excavation is composed of three types of slope forming materials, namely soil, soft rock and rock. Slopes with soft rock material can be formed with a fairly upright slope but are easily degraded when exposed to air and due to surface water erosion. Soft rock slopes whose surfaces are easily degraded often cause problems around the road body, whether surface erosion, shallow landslides or collapsing ruble in some places. Concrete-crib technology is an alternative technology that can be applied to slopes formed from soft rock material. This technology, as a protection measure for erosive soft rock slopes, is built by making concrete cribs that are cast on the spot. Cast-in-place concrete crib wall has a high bending strength, because the beam structure uses reinforced iron. The dimensions of the concrete-crib are 30 cm high and 20 cm wide with a space 150 cm between crib, and iron anchor rods with a depth of 100-150 cm to prevent the collapse of the concrete crib construction due to the load itself. Concrete-crib technology has been applied at Gunung Botak, Manokwari, West Papua Province in 2017 and performance monitoring was carried out in 2018. Based on the results of the monitoring performance of concrete-crib technology during 2018 showing the slope of the fixed concrete-crib construction and the surface of the slope below not degraded, in other words geometric slope is fixed, this shows that concrete-crib technology can withstand the rate of degradation of soft rock slope surface when exposed to air or due to erosion of surface water flow. Key words: road slope, soft rock, slope failure, concrete-crib, performance monitoring